The institutional development of International Association of Academies of Sciences: from scientific councils to international scientific-technological consortia - Vityaz, Petr A.; Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2020)
The article considers the history of creation of formal and informal institutional structures of International Association of the Academies of sciences (IAAS) the functioning of which is based on the technological chains of cognition that are characteristic of traditional disciplinary science. The differences between the technological chains of cognition and the global value chains that have developed in the global economy are shown. The prospects of combining the chains of these types within the framework of international scientific and technological consortia, which are more consistent with the requirements of modern technoscience, are determined. The conclusion is substantiated that the creation of a number of international scientific-technological consortia on the basis of scientific councils of association will allow IAAS to receive a stable source of its additional financing.
Keywords: International Association of Academies of Sciences; institutional structures; knowledge chains; value chains; scientific councils; international scientific-technological consortia